Application of Bibliometric Visualization and Mind Mapping for Dadih Development - Mutia Sari, Shinta; Amini, Hijratun; Saraswati, Lucia; Rozi, Fachrur; Nazir, Novizar; Azima, Fauzan; Rahmayani, Rahmayani (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
Beneficial lactic acid bacteria (LAB) are used to produce dadih, contributing to its health benefits. Dadih is fermented with lactic acid bacteria that convert lactose into glucose and galactose, enhancing digestibility. Despite its potential, dadih has limited appeal due to its traditional production methods and restricted market availability. To address this issue, the article suggests employing methodical concept development techniques, such as Mind Mapping, to generate innovative ideas for dadih product development. In addition, bibliometric analysis is used to obtain insight into the research trends and prospects in the field of food technology as they pertain to local fermented dadih products. The findings from the VOSviewer analysis reveal various aspects of dadih research, including mutagenicity, food safety, and fermented dairy products. Using these insights and mind-mapping techniques, this study advances dadih product development knowledge and is a foundation for future research.